Maternal smoking and the risk of still birth: systematic review and meta-analysis - Marufu, Takawira C.; Ahankari, Anand S.; Coleman, Tim; Lewis, Sarah (BioMed Central, 2015)
BACKGROUND: Smoking in pregnancy is known to be associated with a range of adverse pregnancy outcomes, yet there is a high prevalence of smoking among pregnant women in many countries, and it remains a major public health concern. We have conducted a systematic review and meta-analysis to provide contemporary estimates of the association between maternal smoking in pregnancy and the risk of stillbirth.